Respuesta :

Answer:

0 = -3

Step-by-step explanation:

Subtract 3 from both sides of the equation

8x + 3 - 3 = 8x -3

Simplify

8x = 8x -3

Subtract 8x from both sides of the equation

8x - 8x = 8x - 3 - 8x

Simplify

Combine Like Terms

0 = -3

Answer:

No solution.

Step-by-step explanation:

8x + 3 = 8x

Subtract 8x from both sides of the equation:

8x + 3 - 8x = 8x - 8x

0 + 3 = 0

3 = 0 is a false statement, that is why there is no solution to the original equation, 8x + 3 = 8x.

Hope this helps!